Ionic-liquid doping enables high transconductance, fast response time, and high ion sensitivity in organic electrochemical transistors - Wu, Xihu (2020)
Organic electrochemical transistors (OECTs) are highly attractive for applications ranging from circuit elements and neuromorphic devices to transducers for biological sensing, and the archetypal channel material is poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate), PEDOT:PSS. The operation of OECTs involves the doping and dedoping of a conjugated polymer due to ion intercalation under the application of a gate voltage. However, the challenge is the trade-off in morphology for mixed conduction since good electronic charge transport requires a high degree of ordering among PEDOT chains, while efficient ion uptake and volumetric doping necessitates open and loose packing of the polymer chains. Ionic-liquid-doped PEDOT:PSS that overcomes this limitation is demonstrated. Ionic-liquid-doped OECTs show high transconductance, fast transient response, and high device stability over 3600 switching cycles. The OECTs are further capable of having good ion sensitivity and robust toward physical deformation. These findings pave the way for higher performance bioelectronics and flexible/wearable electronics.